2008
DOI: 10.1143/jjap.47.1931
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectroscopy of Chemical Reaction of 3d Metal Clusters Involved in Chemical Vapor Deposition Synthesis of Carbon Nanotubes

Abstract: The chemical reactions of transition metal clusters in the gas phase have aroused considerable scientific interest and are also of critical scientific importance. For example, these reactions are involved in the synthesis of single-walled carbon nanotubes, which are considered ideal materials because of their outstanding properties. Alcohol catalytic chemical vapor deposition (ACCVD) is one of the best synthetic processes for carbon nanotubes (CNTs); however, even the initial growth mechanism is still unclear,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In order to understand the effect of the carbon precursor molecules and additives described above, it is important to investigate the dissociation process of the carbon precursor molecules on the catalytic metals. Recent in-situ mass spectroscopic analysis [29][30][31] revealed some aspects of the dissociation of carbon precursor molecules during CNT growth by CCVD, in which ethylene molecules and acetylene molecules are key products of the dissociation of ethanol molecules [31]. However, it has not been easy to observe such reaction processes directly during the CCVD process, because it takes place at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the effect of the carbon precursor molecules and additives described above, it is important to investigate the dissociation process of the carbon precursor molecules on the catalytic metals. Recent in-situ mass spectroscopic analysis [29][30][31] revealed some aspects of the dissociation of carbon precursor molecules during CNT growth by CCVD, in which ethylene molecules and acetylene molecules are key products of the dissociation of ethanol molecules [31]. However, it has not been easy to observe such reaction processes directly during the CCVD process, because it takes place at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the addition of a small amount of water during the CVD process enhances the activity and lifetime of the catalytic metal drastically, which enables the synthesis of nanotube forests with heights of up to 2.5 mm repeatedly [5]. In order to understand the dissociation of hydrocarbons and alcohols on the metal cluster, the mass spectroscopic analyses [6][7][8][9][10][11] have been widely employed. For example, an in situ mass spectroscopic analysis during the alcohol CCVD process revealed that ethylene molecules are formed by the ethanol dissociation, which suggests that the C O bond dissociation occurs at the initial stage of the CNT synthesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge these are the first experimental studies on CNT growth employing size-selected, sub-nm iron clusters as catalyst or precatalyst precursors. (A study of 3-D metal clusters as catalysts in CNT growth was reported in [ 8 ], however, no CNT growth was studied therein; CNT growth derived from nm-sized, ligand-stabilized mixed metal clusters as precatalysts was reported in [ 9 ].) Non-agglomerated naked iron clusters of 0.6–0.9 nm size were generated, mass-selected and surface-implanted at room temperature under ultrahigh vacuum [ 10 ] at a surface coverage in the range of a few thousandths up to a few hundredths of a monolayer on standard substrate grids for transmission electron microscopy (TEM).…”
Section: Resultsmentioning
confidence: 99%